EFEK MODEL PEMBELAJARAN KONSTRUKTIVIS KOGNITIF-SOSIAL DAN NON-KONSTRUKTIVIS KONVENSIONAL TERHADAP HASIL BELAJAR FISIKA DASAR MAHASISWA PROGRAM S1 PMIPA LPTK-FKIP UNIVERSITAS - Harahap, Mara Bangun (2010)
The dissertation constitutes the report of the study on instructional model comparison of Social-Cognitive Constructivist (SCC) model with Non-Constructivist Conventional (NCC) model in increasing the Basic Physics achievement of undergraduate students program of Mathematics and Natural Sciences Education (MNSE) on Teacher Training Institution of Teacher Training and Education Faculty (TTI-TTEF) of University. The SCC instructional model is based on the cognitive and social constructivism and it contains four activities, i.e. Invitation, Exploration, submission of Explanation and Solution and Action-making. The SCC instructional model was designed and constructed by researcher. The NCC instructional model is an instructional model in the form of a set learning processes that is consisted of four activity phases, i.e. Orientation, Training, Feed Back and Follow Up. The method of research is experimental-based factorial design 2 x 2. The hypothesis of research was tested by using the statistical analysis of covariant analysis. The study was done on a TTI in Medan, Province of North Sumatera. The population of research are the students of Basic Physics of TTI. The subject of sample consist of 58 students whose educational background in the senior high school was biological program (A2), and 55 students from physics program (A1). The finding of reveals that: The SCC instructional model is statistically significant (p-level = .05) better than NCC instructional model in increasing: Physics Concrete and Formal Abilities (PCFA), Scientific Conception (SC), and Conceptual Change (CC). About more than an half students in teaching with the SCC model and less than an half students in teaching with the NCC were successful to achieve the PCFA score that is higher than average classification. About an half students in teaching with the SCC instructional model and very less than an half students in teaching with the NCC were successful to achieve the SC sore that is higher than average classification. In totality the amount of irrelevant conception type emerged on the group of students whom were taught with SCC instructional model was very less than amount of irrelevant conception type emerged on the group of students whom were taught with the NCC instructional. Beside that, it's revealed that most lecturers of Basic Physics in TTI of the research location did not know the instructional model that is based on the constructivism theoretical foundation, so that they did not teach students the Basic Physics in good ways base on the constructivism. The SCC instructional model prepared to use as the result of research is recommended as inputs for the lecturers whom are responsible to manage the lectures for First Year of Undergraduate Program of MNSE of TTI-TTEF of University. It's recommended that inputs can be used to design the effective lecture of Basic Physics to achieve the objective of the implementation of the First Year of Undergraduate Program of MNSE of TTI-TTEF of University. The lecturers of Basic Physics who are responsible to monitor the conception of students, in order to teach the students do not have misconception or irrelevant conception, the researcher comments them (lecturers) to use the SCC instructional model for revealing and changing the irrelevant conception of students.